2015
DOI: 10.3892/mmr.2015.4135
|View full text |Cite
|
Sign up to set email alerts
|

Association between xanthine dehydrogenase tag single nucleotide polymorphisms and essential hypertension

Abstract: The present study aimed to investigate the association between xanthine dehydrogenase (XDH) gene polymorphism and essential hypertension in the rural Han Chinese population of Fuxin, Liaoning. Han Chinese individuals, who had lived in rural areas of Fuxin, were selected as subjects for the present study. A total of 521 unrelated patients with hypertension were selected, along with a further 533 unrelated individuals with normal blood pressure, in order to serve as controls. Five tag single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Based on the results reported above, among these genes, we focused our attention on Xdh encoding a xanthine dehydrogenase which is a member of a group of hydroxylases involved in the oxidative metabolism. Namely, this protein is converted to xanthine oxidase, which produces ROS . The FPKM values of Xdh transcripts in the control and DEHP groups are shown in Figure D, and the FPKM values of Xdh in the DEHP groups were significantly upregulated compared with those of the control group.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Based on the results reported above, among these genes, we focused our attention on Xdh encoding a xanthine dehydrogenase which is a member of a group of hydroxylases involved in the oxidative metabolism. Namely, this protein is converted to xanthine oxidase, which produces ROS . The FPKM values of Xdh transcripts in the control and DEHP groups are shown in Figure D, and the FPKM values of Xdh in the DEHP groups were significantly upregulated compared with those of the control group.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies demonstrated that XDH and xanthine oxidase (XO) are single gene products, which exist in a single, interconvertible form . XDH was transformed into XO by reversible sulfhydryl oxidation or irreversible proteolytic modification, and both of them are related to the production of ROS . It was reported that the activities of XDH and XO in irradiated rats were significantly increased, while hepatic glutathione content, superoxide dismutase, and catalase were significantly decreased .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…XDH involves in the oxidative purine metabolism by catalyzing hypoxanthine to produce xanthine and ROS [26,27], and the activation of XDH generates oxidative stress [28]. We examined uorescent probe DCF (2',7'-dichloro uorescein, DCF) uorescence intensity represented as ROS level in RCC cells, the results showed that DCF uorescence was signi cantly decreased in C1QBP knockdown ACHN and 786-O cell lines (Fig.…”
Section: C1qbp Modulates Ros Level and Apoptosis In Rccmentioning
confidence: 99%